2013
DOI: 10.1007/s13361-013-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Competing H3PO4 Versus HPO3 + H2O Neutral Losses from Regioselective 18O-Labeled Phosphopeptides

Abstract: Abundant neutral losses of 98 Da are often observed upon ion trap CID-MS/MS of protonated phosphopeptide ions. Two competing fragmentation pathways are involved in this process, namely, the direct loss of H3PO4 from the phosphorylated residue and the combined losses of HPO3 and H2O from the phosphorylation site and from an additional site within the peptide, respectively. These competing pathways produce product ions with different structures but the same m/z values, potentially limiting the utility of CID-MS(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…Indeed, single replacements tend to slightly lower the observed neutral loss rather than increase it. This is in agreement with the observations of Cui, et al who found that mutating acidic residues did not significantly affect neutral loss [17]. It should be noted the presence of one acidic residue greatly increases the chances of finding more acidic residues due to the presence of acidophilic kinase motifs in biological data sets.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, single replacements tend to slightly lower the observed neutral loss rather than increase it. This is in agreement with the observations of Cui, et al who found that mutating acidic residues did not significantly affect neutral loss [17]. It should be noted the presence of one acidic residue greatly increases the chances of finding more acidic residues due to the presence of acidophilic kinase motifs in biological data sets.…”
Section: Resultssupporting
confidence: 92%
“…This has been proposed as the mechanism for neutral loss of HPO 3 in pTyr [36, 37]. Reactions of this kind would be compatible with previous experiments which indicate that a competing neutral loss reaction pathway exists in which HPO 3 is lost from the phosphoresidue concomitantly with the loss of water from elsewhere in the peptide [17]. This reaction would be isobaric and indistinguishable from neutral loss of phosphoric acid.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The neutral loss involves 2 competing cleavages of the phosphoester bond resulting in product ions with different structures but identical m/z values. First, there is a direct loss of H 3 PO 4 (98 Da) from the phosphorylated residue, secondly there is a combined loss of HPO 3 (80 Da) and H 2 O (18 Da) from the phosphorylation site and from an additional site within the peptide, respectively 35 . Indeed, the CID-MS/MS spectrum of the modified tryptic GS-linker peptide included an intense precursor ion signal with a −98 Da loss (pre(−98) + , m/z 1664.8) (Fig.…”
Section: Resultsmentioning
confidence: 99%